A Barcoded Flow Cytometric Assay to Explore the Antibody Responses Against SARS-CoV-2 Spike and Its Variants - Vesper, Niklas; Ortiz, Yaneth; Bartels-Burgahn, Frauke; Yang, Jianying; De La Rosa, Kathrin; Tenbusch, Matthias; Schulz, Sebastian; Finzel, Stephanie; Jäck, Hans-Martin; Eibel, Hermann; Voll, Reinhard E.; Reth, Michael (Frontiers in Immunology, 2021)
The SARS-CoV-2 pandemic has spread to all parts of the world and can cause life-threatening pneumonia and other severe disease manifestations known as COVID-19. This health crisis has resulted in a significant effort to stop the spread of this new coronavirus. However, while propagating itself in the human population, the virus accumulates mutations and generates new variants with increased fitness and the ability to escape the human immune response. Here we describe a color-based barcoded spike flow cytometric assay (BSFA) that is particularly useful to evaluate and directly compare the humoral immune response directed against either wild type (WT) or mutant spike (S) proteins or the receptor-binding domains (RBD) of SARS-CoV-2. This assay employs the human B lymphoma cell line Ramos, transfected for stable expression of WT or mutant S proteins or a chimeric RBD-CD8 fusion protein. We find that the alpha and beta mutants are more stably expressed than the WT S protein on the Ramos B cell surface and/or bind with higher affinity to the viral entry receptor ACE2. However, we find a reduce expression of the chimeric RBD-CD8 carrying the point mutation N501Y and E484K characteristic for the alpha and beta variant, respectively. The comparison of the humoral immune response of 12 vaccinated probands with 12 COVID-19 patients shows that after the boost, the S-specific IgG class immune response in the vaccinated group is similar to that of the patient group. However, in comparison to WT the specific IgG serum antibodies bind less well to the alpha variant and only poorly to the beta variant S protein. This is in line with the notion that the beta variant is an immune escape variant of SARS-CoV-2. The IgA class immune response was more variable than the IgG response and higher in the COVID-19 patients than in the vaccinated group. In summary, we think that our BSFA represents a useful tool to evaluate the humoral immunity against emerging variants of SARS-CoV-2 and to analyze new vaccination protocols against these variants.
CRIS-Team Scopus Importer:2021-10-22
Keywords: coronavirus; COVID-19; flow cytometry; humoral immunity; RBD; SARS-CoV-2; spike protein; virus variants

ACE2-independent sarbecovirus cell entry can be supported by TMPRSS2-related enzymes and can reduce sensitivity to antibody-mediated neutralization - Zhang, Lu; Cheng, Hsiu Hsin; Krüger, Nadine; Hörnich, Bojan; Graichen, Luise; Hahn, Alexander S.; Schulz, Sebastian; Jäck, Hans-Martin; Stankov, Metodi V.; Behrens, Georg M.N.; Müller, Marcel A.; Drosten, Christian; et al. (PLoS Pathogens, 2024)
The COVID-19 pandemic, caused by SARS-CoV-2, demonstrated that zoonotic transmission of animal sarbecoviruses threatens human health but the determinants of transmission are incompletely understood. Here, we show that most spike (S) proteins of horseshoe bat and Malayan pangolin sarbecoviruses employ ACE2 for entry, with human and raccoon dog ACE2 exhibiting broad receptor activity. The insertion of a multibasic cleavage site into the S proteins increased entry into human lung cells driven by most S proteins tested, suggesting that acquisition of a multibasic cleavage site might increase infectivity of diverse animal sarbecoviruses for the human respiratory tract. In contrast, two bat sarbecovirus S proteins drove cell entry in an ACE2-independent, trypsin-dependent fashion and several ACE2-dependent S proteins could switch to the ACE2-independent entry pathway when exposed to trypsin. Several TMPRSS2-related cellular proteases but not the insertion of a multibasic cleavage site into the S protein allowed for ACE2-independent entry in the absence of trypsin and may support viral spread in the respiratory tract. Finally, the pan-sarbecovirus antibody S2H97 enhanced cell entry driven by two S proteins and this effect was reversed by trypsin while trypsin protected entry driven by a third S protein from neutralization by S2H97. Similarly, plasma from quadruple vaccinated individuals neutralized entry driven by all S proteins studied, and availability of the ACE2-independent, trypsin-dependent pathway reduced neutralization sensitivity. In sum, our study reports a pathway for entry into human cells that is ACE2-independent, can be supported by TMPRSS2-related proteases and may be associated with antibody evasion.
CRIS-Team Scopus Importer:2024-11-22

Affinity maturation endows potent activity onto class 6 SARS-CoV-2 broadly neutralizing antibodies - Mazigi, Ohan; Langley, David B.; Henry, Jake Y.; Burnett, Deborah L.; Sobti, Meghna; Walker, Gregory J.; Rouet, Romain; Balachandran, Harikrishnan; Lenthall, Helen; Jackson, Jennifer; Ubiparipovic, Stephanie; Schofield, Peter; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2025)
The emergence of SARS-CoV-2 variants of concern (VOCs) has greatly diminished the neutralizing activity of previously FDA-approved monoclonal antibodies (mAbs), including that of antibody cocktails and of first-generation broadly neutralizing antibodies such as S309 (Sotrovimab). In contrast, antibodies targeting cryptic conformational epitopes of the receptor binding domain (RBD) have demonstrated broad activity against emerging variants, but exert only moderate neutralizing activity, which has so far hindered clinical development. Here, we utilize in vitro display technology to identify and affinity-mature antibodies targeting the cryptic class 6 epitope, accessible only in the “up” conformation of the SARS-CoV-2 spike trimer. Increasing antibody affinity into the low picomolar range endowed potent neutralization of VOCs and protection of hACE2 mice from viral challenge. Cryoelectron microscopy and crystal structures of two affinity-matured antibodies (4C12-B12 and 4G1-C2) in complex with RBD highlighted binding modes and epitopes distal from mutational hotspots commonly overserved in VOCs, providing direct structural insights into the observed mutational resistance. Moreover, we further demonstrate that antibodies targeting the class 6 epitope, rather than being an artifact of in vitro selection, are common in the IgG1+ memory B cell repertoire of convalescent patients and can be induced in human antibody V-gene transgenic mice through immunization. Our results highlight the importance of very high (picomolar) affinity in the development of neutralizing antibodies and vaccines and suggest an affinity threshold in the provision of broad and long-lasting immunity against SARS-CoV-2.
CRIS-Team Scopus Importer:2025-01-31
Keywords: antibody; COVID; immunity

A new staining protocol for detection of murine antibody-secreting plasma cell subsets by flow cytometry - Pracht, Katharina; Meinzinger, Julia; Daum, Patrick; Schulz, Sebastian; Reimer, Dorothea; Hauke, Manuela; Roth, Edith; Mielenz, Dirk; Berek, Claudia; Corte-Real, Joana; Jäck, Hans-Martin; Schuh, Wolfgang (European Journal of Immunology, 2017)
We provide a robust four-color fluorescence-based flow cytometry protocol that distinguishes viable dividing plasmablasts from nondividing plasma cells and, based on CD19 surface abundance, identifies two mature plasma cell populations in the spleen and the bone marrow of mice.
EVALuna2:13650

A pair of non‐competing neutralizing human monoclonal antibodies protecting from disease in a SARS‐CoV‐2 infection model - Peter, Antonia Sophia; Roth, Edith; Schulz, Sebastian; Fraedrich, Kirsten; Steinmetz, Tobit; Damm, Dominik; Hauke, Manuela; Richel, Elie; Müller-Schmucker, Sandra; Habenicht, Katharina Marie; Eberlein, Valentina; Issmail, Leila; et al. (European Journal of Immunology, 2021)
TRIANNI mice carry an entire set of human immunoglobulin V region gene segments and are a powerful tool to rapidly isolate human monoclonal antibodies. After immunizing these mice with DNA encoding the spike protein of SARS-CoV-2 and boosting with spike protein, we identified 29 hybridoma antibodies that reacted with the SARS-CoV-2 spike protein. Nine antibodies neutralize SARS-CoV-2 infection at IC50 values in the subnanomolar range. ELISA-binding studies and DNA sequence analyses revealed one cluster of three clonally related neutralizing antibodies that target the receptor-binding domain and compete with the cellular receptor hACE2. A second cluster of six clonally related neutralizing antibodies bind to the N-terminal domain of the spike protein without competing with the binding of hACE2 or cluster 1 antibodies. SARS-CoV-2 mutants selected for resistance to an antibody from one cluster are still neutralized by an antibody from the other cluster. Antibodies from both clusters markedly reduced viral spread in mice transgenic for human ACE2 and protected the animals from SARS-CoV-2-induced weight loss. The two clusters of potent non-competing SARS-CoV-2 neutralizing antibodies provide potential candidates for therapy and prophylaxis of COVID-19. The study further supports transgenic animals with a human immunoglobulin gene repertoire as a powerful platform in pandemic preparedness initiatives.

Association of Circulating Antibody-Secreting Cell Maturity With Disease Features in Primary Sjogren's Syndrome - Steinmetz, Tobit D.; Verstappen, Gwenny M.; Schulz, Sebastian; De Wolff, Liseth; Wilbrink, Rick; Visser, Annie; Terpstra, Janneke; Bootsma, Hendrika; Kroese, Frans G. M. (Arthritis and Rheumatology, 2023)
Objective. B cell hyperactivity plays an important role in primary Sjogren's syndrome (SS). We undertook this study to better understand the B cell effector branch, namely antibody-secreting cells (ASCs) in primary SS, and to examine the quantity, maturity, and inflammatory properties of ASCs in primary SS patients.
CRIS-Team WoS Importer:2023-04-21

A surrogate cell-based SARS-CoV-2 spike blocking assay - Schuh, Wolfgang; Baus, Lena; Steinmetz, Tobit; Schulz, Sebastian; Weckwerth, Leonie; Roth, Edith; Hauke, Manuela; Krause, Stefan; Morhart, Patrick; Rauh, Manfred; Hoffmann, Markus; Vesper, Niklas; et al. (European Journal of Immunology, 2021)
To monitor infection by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and successful vaccination against coronavirus disease 2019 (COVID-19), the kinetics of neutralizing or blocking anti-SARS-CoV-2 antibody titers need to be assessed. Here, we report the development of a quick and inexpensive surrogate SARS-CoV-2 blocking assay (SUBA) using immobilized recombinant human angiotensin-converting enzyme 2 (hACE2) and human cells expressing the native form of surface SARS-CoV-2 spike protein. Spike protein-expressing cells bound to hACE2 in the absence or presence of blocking antibodies were quantified by measuring the optical density of cell-associated crystal violet in a spectrophotometer. The advantages are that SUBA is a fast and inexpensive assay, which does not require biosafety level 2- or 3-approved laboratories. Most importantly, SUBA detects blocking antibodies against the native trimeric cell-bound SARS-CoV-2 spike protein and can be rapidly adjusted to quickly pre-screen already approved therapeutic antibodies or sera from vaccinated individuals for their ACE2 blocking activities against any emerging SARS-CoV-2 variants.
CRIS-Team Scopus Importer:2021-10-08
Keywords: COVID-19; hACE2; SARS-CoV-2; Spike protein; Surrogate blocking assay

Augmented neutralisation resistance of emerging omicron subvariants BA.2.12.1, BA.4, and BA.5 - Arora, Prerna; Kempf, Amy; Nehlmeier, Inga; Schulz, Sebastian; Cossmann, Anne; Stankov, Metodi V.; Jäck, Hans-Martin; Behrens, Georg M.N.; Pöhlmann, Stefan; Hoffmann, Markus (Lancet Infectious Diseases, 2022)
CRIS-Team Scopus Importer:2022-08-05

Augmented neutralization of SARS-CoV-2 Omicron variant by boost vaccination and monoclonal antibodies - Schulz, Sebastian; Hoffmann, Markus; Roth, Edith; Pracht, Katharina; Burnett, Deborah L.; Mazigi, Ohan; Schuh, Wolfgang; Manger, Bernhard; Mielenz, Dirk; Goodnow, Christopher C.; Christ, Daniel; Poehlmann, Stefan; et al. (European Journal of Immunology, 2022)
Effective vaccines and monoclonal antibodies have been developed against coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, the appearance of virus variants with higher transmissibility and pathogenicity is a major concern because of their potential to escape vaccines and clinically approved SARS-CoV-2- antibodies. Here, we use flow cytometry-based binding and pseudotyped SARS-CoV-2 neutralization assays to determine the efficacy of boost immunization and therapeutic antibodies to neutralize the dominant Omicron variant. We provide compelling evidence that the third vaccination with BNT162b2 increases the amount of neutralizing serum antibodies against Delta and Omicron variants, albeit to a lower degree when compared to the parental Wuhan strain. Therefore, a third vaccination is warranted to increase titers of protective serum antibodies, especially in the case of the Omicron variant. We also found that most clinically approved and otherwise potent therapeutic antibodies against the Delta variant failed to recognize and neutralize the Omicron variant. In contrast, some antibodies under preclinical development potentially neutralized the Omicron variant. Our studies also support using a flow cytometry-based antibody binding assay to rapidly monitor therapeutic candidates and serum titers against emerging SARS-CoV-2 variants.
CRIS-Team WoS Importer:2022-04-08

B.1.617.2 enters and fuses lung cells with increased efficiency and evades antibodies induced by infection and vaccination - Arora, Prerna; Sidarovich, Anzhalika; Krüger, Nadine; Kempf, Amy; Nehlmeier, Inga; Graichen, Luise; Moldenhauer, Anna Sophie; Winkler, Martin S.; Schulz, Sebastian; Jäck, Hans-Martin; Stankov, Metodi V.; Behrens, Georg M.N.; et al. (Cell Reports, 2021)
The Delta variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), B.1.617.2, emerged in India and has spread to over 80 countries. B.1.617.2 replaced B.1.1.7 as the dominant virus in the United Kingdom, resulting in a steep increase in new infections, and a similar development is expected for other countries. Effective countermeasures require information on susceptibility of B.1.617.2 to control by antibodies elicited by vaccines and used for coronavirus disease 2019 (COVID-19) therapy. We show, using pseudotyping, that B.1.617.2 evades control by antibodies induced upon infection and BNT162b2 vaccination, although to a lesser extent as compared to B.1.351. We find that B.1.617.2 is resistant against bamlanivimab, a monoclonal antibody with emergency use authorization for COVID-19 therapy. Finally, we show increased Calu-3 lung cell entry and enhanced cell-to-cell fusion of B.1.617.2, which may contribute to augmented transmissibility and pathogenicity of this variant. These results identify B.1.617.2 as an immune evasion variant with increased capacity to enter and fuse lung cells.
CRIS-Team Scopus Importer:2021-10-22
Keywords: antibody; B.1.617.2; COVID-19; neutralization; SARS-CoV-2; spike

B Cell Speed and B-FDC Contacts in Germinal Centers Determine Plasma Cell Output via Swiprosin-1/EFhd2 - Reimer, Dorothea; Meyer-Hermann, Michael; Rakhymzhan, Asylkhan; Steinmetz, Tobit; Tripal, Philipp; Thomas, Jana; Böttcher, Martin; Mougiakakos, Dimitrios; Schulz, Sebastian; Urbanczyk, Sophia; Hauser, Anja E.; Niesner, Raluca A.; et al. (Cell Reports, 2020)
Plasma cells secreting affinity-matured antibodies develop in germinal centers (GCs), where B cells migrate persistently and directionally over defined periods of time. How modes of GC B cell migration influence plasma cell development remained unclear. Through genetic deletion of the F-actin bundling protein Swiprosin-1/EF-hand domain family member 2 (EFhd2) and by two-photon microscopy, we show that EFhd2 restrains B cell speed in GCs and hapten-specific plasma cell output. Modeling the GC reaction reveals that increasing GC B cell speed promotes plasma cell generation. Lack of EFhd2 also reduces contacts of GC B cells with follicular dendritic cells in vivo. Computational modeling uncovers that both GC output and antibody affinity depend quantitatively on contacts of GC B cells with follicular dendritic cells when B cells migrate more persistently. Collectively, our data explain how GC B cells integrate speed and persistence of cell migration with B cell receptor affinity.
CRIS-Team Scopus Importer:2020-08-14
Keywords: actin cytoskeleton; B cell receptor; differentiation; follicular dendritic cell; germinal center; migration; plasma cell; selection; Swiprosin-1/EFhd2; synapse

Comparable neutralisation evasion of SARS-CoV-2 omicron subvariants BA.1, BA.2, and BA.3 - Arora, Prerna; Zhang, Lu; Rocha, Cheila; Sidarovich, Anzhalika; Kempf, Amy; Schulz, Sebastian; Cossmann, Anne; Manger, Bernhard; Baier, Eva; Tampe, Björn; Moerer, Onnen; Dickel, Steffen; et al. (Lancet Infectious Diseases, 2022)
CRIS-Team Scopus Importer:2022-06-03

Comparative Analysis of Host Cell Entry Efficiency and Neutralization Sensitivity of Emerging SARS-CoV-2 Lineages KP.2, KP.2.3, KP.3, and LB.1 - Chen, Nianzhen; Decker, Katharina Emma; Schulz, Sebastian; Kempf, Amy; Nehlmeier, Inga; Moldenhauer, Anna Sophie; Dopfer-Jablonka, Alexandra; Behrens, Georg M.N.; Stankov, Metodi V.; Manthey, Luis; Jäck, Hans-Martin; Hoffmann, Markus; et al. (Vaccines, 2024)
New SARS-CoV-2 lineages continue to evolve and may exhibit new characteristics regarding host cell entry efficiency and potential for antibody evasion. Here, employing pseudotyped particles, we compared the host cell entry efficiency, ACE2 receptor usage, and sensitivity to antibody-mediated neutralization of four emerging SARS-CoV-2 lineages, KP.2, KP.2.3, KP.3, and LB.1. The XBB.1.5 and JN.1 lineages served as controls. Our findings reveal that KP.2, KP.2.3, KP.3, and LB.1 lineages enter host cells efficiently and in an ACE2-dependent manner, and that KP.3 is more adept at entering Calu-3 lung cells than JN.1. However, the variants differed in their capacity to employ ACE2 orthologues from animal species for entry, suggesting differences in ACE2 interactions. Moreover, we demonstrate that only two out of seven therapeutic monoclonal antibody (mAbs) in preclinical development retain robust neutralizing activity against the emerging JN.1 sublineages tested, while three mAbs displayed strongly reduced neutralizing activity and two mAbs lacked neutralizing activity against any of the lineages tested. Furthermore, our results show that KP.2, KP.2.3, KP.3, and LB.1 lineages evade neutralization by antibodies induced by infection or vaccination with greater efficiency than JN.1, particularly in individuals without hybrid immunity. This study indicates that KP.2, KP.2.3, KP.3, and LB.1 differ in ACE2 interactions and the efficiency of lung cell entry and suggest that evasion of neutralizing antibodies drove the emergence of these variants.
CRIS-Team Scopus Importer:2025-02-04
Keywords: ACE2 receptor interactions; antibody evasion; SARS-CoV-2 lineages

Decoding plasma cell maturation dynamics with BCMA - Schulz, Sebastian; Menzel, Shannon; Wittner, Jens; Ulbricht, Carolin; Grofe, Alina T.; Roth, Edith; Mann-Nüttel, Ritu; Scheu, Stefanie; Kueh, Andrew J.; Jäck, Alexander; Herold, Marco J.; Hauser, Anja E.; et al. (Frontiers in Immunology, 2025)
Plasma cells provide protective antibodies following an infection or vaccination. A network of intrinsic and extrinsic factors fine-tunes the generation of a heterogenous plasma cell pool with varying metabolic requirements, transcriptional profiles and lifespans. Among these, the B cell maturation antigen (BCMA) has been implicated in the APRIL-mediated survival of long-lived plasma cells. To characterize the terminal maturation of plasma cells, we constructed a BCMA reporter mouse (BCMA:Tom) that exclusively labeled antibody-secreting cells and revealed that BCMA:Tom expression varied by IgH isotype and increased with plasma cell maturity. The BCMA reporter, used alongside the Blimp1-GFP reporter, also allowed detailed tracking of plasma cell development and highlighted the importance of the in vivo microenvironment to complete plasma cell maturation. Therefore, the BCMA:Tom reporter mouse provides a valuable tool for tracking plasma cell development and maturation with flow cytometry or advanced imaging techniques, enabling a deeper understanding of the mechanisms regulating plasma cell heterogeneity and longevity.
CRIS-Team Scopus Importer:2025-04-01
Keywords: antibody-secreting cells (ASC); BCMA (TNFRSF17); bone marrow; plasma cells; spleen; survival; thymus

Delta variant (B.1.617.2) sublineages do not show increased neutralization resistance - Arora, Prerna; Kempf, Amy; Nehlmeier, Inga; Graichen, Luise; Sidarovich, Anzhalika; Winkler, Martin S.; Schulz, Sebastian; Jäck, Hans-Martin; Stankov, Metodi V.; Behrens, Georg M. N.; Pohlmann, Stefan; Hoffmann, Markus (Cellular & Molecular Immunology, 2021)
CRIS-Team Scopus Importer:2021-10-22

Duration of effectiveness of vaccination against COVID-19 caused by the omicron variant - Arora, Prerna; Kempf, Amy; Nehlmeier, Inga; Schulz, Sebastian; Cossmann, Anne; Stankov, Metodi V.; Jäck, Hans-Martin; Behrens, Georg M. N.; Poehlmann, Stefan; Hoffmann, Markus (Lancet Infectious Diseases, 2022)
CRIS-Team WoS Importer:2023-03-10

Efficient antibody evasion but reduced ACE2 binding by the emerging SARS-CoV-2 variant B.1.640.2 - Arora, Prerna; Kempf, Amy; Nehlmeier, Inga; Graichen, Luise; Schulz, Sebastian; Cossmann, Anne; Dopfer-Jablonka, Alexandra; Winkler, Martin S.; Jäck, Hans-Martin; Behrens, Georg M. N.; Pohlmann, Stefan; Hoffmann, Markus (Cellular & Molecular Immunology, 2022)
CRIS-Team WoS Importer:2022-06-03

Entry Efficiency, Protease Dependence, and Antibody-Mediated Neutralization of SARS-CoV-2 Sublineages KP.3.1.1 and XEC - Arora, Prerna; Kempf, Amy; Nehlmeier, Inga; Schulz, Sebastian; Jäck, Hans-Martin; Hoffmann, Markus; Pöhlmann, Stefan (Vaccines, 2025)
Background: The SARS-CoV-2 variants KP.3.1.1 and XEC currently dominate the COVID-19 epidemic. However, their cell tropism, proteolytic processing, and susceptibility to neutralization by monoclonal antibodies remain incompletely characterized. Methods: We employed pseudotyped viruses to assess the entry efficiency of KP.3.1.1 and XEC in various cell lines, their dependence on TMPRSS2 for lung cell entry, and their ability to use ACE2 for infection. Additionally, we evaluated their susceptibility to neutralization by monoclonal antibodies BD55-4637 and BD55-5514. Results: KP.3.1.1 and XEC entered cell lines with similar efficiency as the parental JN.1 lineage and utilized TMPRSS2 for Calu-3 lung cell entry. Unlike JN.1, KP.3.1.1 and XEC failed to efficiently use murine ACE2 for cell entry. Both variants were effectively neutralized by the monoclonal antibodies BD55-4637 and BD55-5514, suggesting therapeutic potential. Conclusions: Our findings demonstrate that JN.1, KP.3.1.1, and XEC, like their predecessor BA.2.86, rely on TMPRSS2 for lung cell entry and remain sensitive to certain neutralizing monoclonal antibodies. However, these variants differ in their ability to utilize ACE2 species orthologs for cell entry.
CRIS-Team Scopus Importer:2025-05-09
Keywords: BA.2.86 descendants; cell tropism; monoclonal antibody susceptibility; SARS-CoV-2 variants

Evidence for an ACE2-Independent Entry Pathway That Can Protect from Neutralization by an Antibody Used for COVID-19 Therapy - Hoffmann, Markus; Sidarovich, Anzhalika; Arora, Prerna; Krueger, Nadine; Nehlmeier, Inga; Kempf, Amy; Graichen, Luise; Winkler, Martin S.; Niemeyer, Daniela; Goffinet, Christine; Drosten, Christian; Schulz, Sebastian; et al. (Mbio, 2022)
The interaction of the SARS-CoV-2 spike protein (S) with the cellular receptor ACE2 is considered essential for infection and constitutes the key target for antibodies induced upon infection and vaccination. Here, using a surrogate system for viral entry, we provide evidence that a naturally occurring mutation can liberate SARS-CoV-2 from ACE2-dependence and that ACE2-independent entry may protect the virus from neutralization by an antibody used for COVID-19 therapy.
CRIS-Team WoS Importer:2022-05-13

GLUT1-mediated glucose import in B cells is critical for anaplerotic balance and humoral immunity - Bierling, Theresa; Gumann, Amelie; Ottmann, Shannon; Schulz, Sebastian; Weckwerth, Leonie; Thomas, Jana; Geßner, Arne; Wichert, Magdalena; Kuwert, Frederic; Rost, Franziska; Hauke, Manuela; Freudenreich, Tatjana; et al. (Cell Reports, 2024)
Glucose uptake increases during B cell activation and antibody-secreting cell (ASC) differentiation, but conflicting findings prevent a clear metabolic profile at different stages of B cell activation. Deletion of the glucose transporter type 1 (GLUT1) gene in mature B cells (GLUT1-cKO) results in normal B cell development, but it reduces germinal center B cells and ASCs. GLUT1-cKO mice show decreased antigen-specific antibody titers after vaccination. In vitro, GLUT1-deficient B cells show impaired activation, whereas established plasmablasts abolish glycolysis, relying on mitochondrial activity and fatty acids. Transcriptomics and metabolomics reveal an altered anaplerotic balance in GLUT1-deficient ASCs. Despite attempts to compensate for glucose deprivation by increasing mitochondrial mass and gene expression associated with glycolysis, the tricarboxylic acid cycle, and hexosamine synthesis, GLUT1-deficient ASCs lack the metabolites for energy production and mitochondrial respiration, limiting protein synthesis. We identify GLUT1 as a critical metabolic player defining the germinal center response and humoral immunity.
CRIS-Team Scopus Importer:2024-02-23
Keywords: adaptive immune response; antibody-secreting cell; CP: Immunology; CP: Metabolism; glucose transporter type 1; GLUT1; glycolysis; metabolism; mitochondrial respiration; plasma cell; plasmablast

Guidelines for the use of flow cytometry and cell sorting in immunological studies (second edition) - Cossarizza, Andrea; Acs, Andreas; Adam, Dieter; Adam-Klages, Sabine; Agace, William W.; Aghaeepour, Nima; Akdis, Mübeccel; Allez, Matthieu; Almeida, Larissa Nogueira; Alvisi, Giorgia; Anderson, Graham; Andrä, Immanuel; et al. (European Journal of Immunology, 2019)
These guidelines are a consensus work of a considerable number of members of the immunology and flow cytometry community. They provide the theory and key practical aspects of flow cytometry enabling immunologists to avoid the common errors that often undermine immunological data. Notably, there are comprehensive sections of all major immune cell types with helpful Tables detailing phenotypes in murine and human cells. The latest flow cytometry techniques and applications are also described, featuring examples of the data that can be generated and, importantly, how the data can be analysed. Furthermore, there are sections detailing tips, tricks and pitfalls to avoid, all written and peer-reviewed by leading experts in the field, making this an essential research companion.
CRIS-Team Scopus Importer:2019-10-29

Host cell entry and neutralisation sensitivity of the SARS-CoV-2 XBB.1.16 lineage - Nehlmeier, Inga; Kempf, Amy; Arora, Prerna; Cossmann, Anne; Dopfer-Jablonka, Alexandra; Stankov, Metodi V.; Schulz, Sebastian; Jäck, Hans-Martin; Behrens, Georg M.N.; Pöhlmann, Stefan; Hoffmann, Markus (Cellular & Molecular Immunology, 2023)
CRIS-Team Scopus Importer:2023-05-19

Host Cell Entry and Neutralization Sensitivity of SARS-CoV-2 Lineages B.1.620 and R.1 - Sidarovich, Anzhalika; Krueger, Nadine; Rocha, Cheila; Graichen, Luise; Kempf, Amy; Nehlmeier, Inga; Lier, Martin; Cossmann, Anne; Stankov, Metodi; Schulz, Sebastian; Behrens, Georg M. N.; Jäck, Hans-Martin; et al. (Viruses, 2022)
The spike (S) protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) facilitates viral entry into host cells and is the key target for neutralizing antibodies. The SARS-CoV-2 lineage B.1.620 carries fifteen mutations in the S protein and is spread in Africa, the US and Europe, while lineage R.1 harbors four mutations in S and infections were observed in several countries, particularly Japan and the US. However, the impact of the mutations in B.1.620 and R.1 S proteins on antibody-mediated neutralization and host cell entry are largely unknown. Here, we report that these mutations are compatible with robust ACE2 binding and entry into cell lines, and they markedly reduce neutralization by vaccine-induced antibodies. Our results reveal evasion of neutralizing antibodies by B.1.620 and R.1, which might have contributed to the spread of these lineages.
CRIS-Team Scopus Importer:2022-11-25
Keywords: ACE2 binding; antibody evasion; B.1.620; cell entry; neutralization; R.1; SARS-CoV-2; spike protein

Host cell lectins ASGR1 and DC-SIGN jointly with TMEM106B confer ACE2 independence and imdevimab resistance to SARS-CoV-2 pseudovirus with spike mutation E484D - Arora, Prerna; Zhang, Lu; Nehlmeier, Inga; Kempf, Amy; Graichen, Luise; Kreitz, Eike; Sidarovich, Anzhalika; Rocha, Cheila; Gärtner, Sabine; Winkler, Michael; Schulz, Sebastian; Jäck, Hans-Martin; et al. (Journal of Virology, 2025)
The naturally occurring mutation E484D in the spike (S) protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can render viral entry ACE2 independent and imdevimab resistant. Here, we investigated whether the cellular proteins ASGR1, DC-SIGN, and TMEM106B, which interact with the viral S protein, can contribute to these processes. Employing S protein-pseudotyped particles, we found that expression of ASGR1 or DC-SIGN jointly with TMEM106B allowed for robust entry of mutant E484D into otherwise non-susceptible cells, while this effect was not observed upon separate expression of the single proteins and upon infection with SARS-CoV-2 wild type (WT). Furthermore, expression of ASGR1 or DC-SIGN conferred ACE2 independence and imdevimab resistance to entry of mutant E484D but not WT, and entry under those conditions was dependent on endogenous TMEM106B. These results suggest that engagement of certain cellular lectins can direct SARS-CoV-2 mutant E484D to an ACE2-independent, TMEM106B-dependent entry pathway that is not inhibited by imdevimab.IMPORTANCEThe interaction of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein with the ACE2 receptor determines the viral cell tropism and is the key target of the neutralizing antibody response. Here, we show that SARS-CoV-2 with a single, naturally occurring mutation in the spike protein, E484D, can use the cellular lectins ASGR1 and DC-SIGN in conjunction with TMEM106B for ACE2-independent entry and evasion of therapeutic antibodies. These results suggest that engagement of cellular lectins might modulate target cell choice of SARS-CoV-2 and might allow evasion of certain neutralizing antibodies.
CRIS-Team Scopus Importer:2025-03-14
Keywords: entry; lectin; neutralization; SARS-CoV-2; spike

Identification of TFG- and Autophagy-Regulated Proteins and Glycerophospholipids in B Cells - Steinmetz, Tobit; Thomas, Jana; Reimann, Lena; Himmelreich, Ann-Kathrin; Schulz, Sebastian; Golombek, Florian; Castiglione, Kathrin; Jäck, Hans-Martin; Brodesser, Susanne; Warscheid, Bettina; Mielenz, Dirk (Journal of Proteome Research, 2024)
Keywords: metabolism; lysosome; JCHAIN; immunoglobulin; TRK-fused gene; ribosome; plasma cell; phosphatidylglycerol; autophagy; BCL10; endoplasmic reticulum stress; autophagy flux; B cell

Immunizations with diverse sarbecovirus receptor-binding domains elicit SARS-CoV-2 neutralizing antibodies against a conserved site of vulnerability - Burnett, Deborah L.; Jackson, Katherine J.L.; Langley, David B.; Aggrawal, Anupria; Stella, Alberto Ospina; Johansen, Matt D.; Balachandran, Harikrishnan; Lenthall, Helen; Rouet, Romain; Walker, Gregory; Saunders, Bernadette M.; Singh, Mandeep; et al. (Immunity, 2021)
Viral mutations are an emerging concern in reducing SARS-CoV-2 vaccination efficacy. Second-generation vaccines will need to elicit neutralizing antibodies against sites that are evolutionarily conserved across the sarbecovirus subgenus. Here, we immunized mice containing a human antibody repertoire with diverse sarbecovirus receptor-binding domains (RBDs) to identify antibodies targeting conserved sites of vulnerability. Antibodies with broad reactivity against diverse clade B RBDs targeting the conserved class 4 epitope, with recurring IGHV/IGKV pairs, were readily elicited but were non-neutralizing. However, rare class 4 antibodies binding this conserved RBD supersite showed potent neutralization of SARS-CoV-2 and all variants of concern. Structural analysis revealed that the neutralizing ability of cross-reactive antibodies was reserved only for those with an elongated CDRH3 that extends the antiparallel beta-sheet RBD core and orients the antibody light chain to obstruct ACE2-RBD interactions. These results identify a structurally defined pathway for vaccine strategies eliciting escape-resistant SARS-CoV-2 neutralizing antibodies.
CRIS-Team Scopus Importer:2021-11-26
Keywords: antigenic variation; class 4 epitope site; cross-reactivity; epitope conservation; escape mutations; human antibodies; mouse model; neutralization; next generation vaccines; SARS-CoV-2; variants of concern

Inhibition of ATM or ATR in combination with hypo-fractionated radiotherapy leads to a different immunophenotype on transcript and protein level in HNSCC - Meidenbauer, Julia; Wachter, Matthias; Schulz, Sebastian; Mostafa, Nada; Zülch, Lilli; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Jost, Tina (Frontiers in Oncology, 2024)
Background: The treatment of head and neck tumors remains a challenge due to their reduced radiosensitivity. Small molecule kinase inhibitors (smKI) that inhibit the DNA damage response, may increase the radiosensitivity of tumor cells. However, little is known about how the immunophenotype of the tumor cells is modulated thereby. Therefore, we investigated whether the combination of ATM or ATR inhibitors with hypo-fractionated radiotherapy (RT) has a different impact on the expression of immune checkpoint markers (extrinsic), the release of cytokines or the transcriptome (intrinsic) of head and neck squamous cell carcinoma (HNSCC) cells. Methods: The toxic and immunogenic effects of the smKI AZD0156 (ATMi) and VE-822 (ATRi) in combination with a hypo-fractionated scheme of 2x5Gy RT on HPV-negative (HSC4, Cal-33) and HPV-positive (UM-SCC-47, UD-SCC-2) HNSCC cell lines were analyzed as follows: cell death (necrosis, apoptosis; detected by AnxV/PI), expression of immunostimulatory (ICOS-L, OX40-L, TNFSFR9, CD70) and immunosuppressive (PD-L1, PD-L2, HVEM) checkpoint marker using flow cytometry; the release of cytokines using multiplex ELISA and the gene expression of Cal-33 on mRNA level 48 h post-RT. Results: Cell death was mainly induced by the combination of RT with both inhibitors, but stronger with ATRi. Further, the immune phenotype of cancer cells, not dying from combination therapy itself, is altered predominantly by RT+ATRi in an immune-stimulatory manner by the up-regulation of ICOS-L. However, the analysis of secreted cytokines after treatment of HNSCC cell lines revealed an ambivalent influence of both inhibitors, as we observed the intensified secretion of IL-6 and IL-8 after RT+ATRi. These findings were confirmed by RNAseq analysis and further the stronger immune-suppressive character of RT+ATMi was enlightened. We detected the down-regulation of a central protein of cytoplasmatic sensing pathways of nucleic acids, RIG-1, and found one immune-suppressive target, EDIL3, strongly up-regulated by RT+ATMi. Conclusion: Independent of a restrictive toxicity, the combination of RT + either ATMi or ATRi leads to comprehensive and immune-modulating alterations in HNSCC. This includes pro-inflammatory signaling induced by RT + ATRi but also anti-inflammatory signals. These findings were confirmed by RNAseq analysis, which further highlighted the immune-suppressive nature of RT + ATMi.
CRIS-Team Scopus Importer:2024-10-25
Keywords: ATM inhibition; ATR inhibition; DNA damage repair; HNSCC; immunomodulation; kinase inhibitors

Inter-domain communication in SARS-CoV-2 spike proteins controls protease-triggered cell entry - Qing, Enya; Li, Pengfei; Cooper, Laura; Schulz, Sebastian; Jäck, Hans-Martin; Rong, Lijun; Perlman, Stanley; Gallagher, Tom (Cell Reports, 2022)
SARS-CoV-2 continues to evolve into variants of concern (VOC), with greatest variability in the multidomain, entry-facilitating spike proteins. To recognize the significance of adaptive spike protein changes, we compare variant SARS-CoV-2 virus particles in several assays reflecting authentic virus-cell entry. Virus particles with adaptive changes in spike amino-terminal domains (NTDs) are hypersensitive to proteolytic activation of membrane fusion, an essential step in virus-cell entry. Proteolysis is within fusion domains (FDs), at sites over 10 nm from the VOC-specific NTD changes, indicating allosteric inter-domain control of fusion activation. In addition, NTD-specific antibodies block FD cleavage, membrane fusion, and virus-cell entry, suggesting restriction of inter-domain communication as a neutralization mechanism. Finally, using structure-guided mutagenesis, we identify an inter-monomer β sheet structure that facilitates NTD-to-FD transmissions and subsequent fusion activation. This NTD-to-FD axis that sensitizes viruses to infection and to NTD-specific antibody neutralization provides new context for understanding selective forces driving SARS-CoV-2 evolution.
CRIS-Team Scopus Importer:2022-05-27
Keywords: coronavirus; CP: Microbiology; membrane fusion; SARS-CoV-2; spike protein; virus entry; virus evolution; virus neutralization; virus variation

Krüppel-like factor 2 controls IgA plasma cell compartmentalization and IgA responses - Wittner, Jens; Schulz, Sebastian; Steinmetz, Tobit; Berges, Johannes; Hauke, Manuela; Channell, William M.; Cunningham, Adam F.; Hauser, Anja E.; Hutloff, Andreas; Mielenz, Dirk; Jäck, Hans-Martin; Schuh, Wolfgang (Mucosal Immunology, 2022)
Krüppel-like factor 2 (KLF2) is a potent regulator of lymphocyte differentiation, activation and migration. However, its functional role in adaptive and humoral immunity remains elusive. Therefore, by using mice with a B cell-specific deletion of KLF2, we investigated plasma cell differentiation and antibody responses. We revealed that the deletion of KLF2 resulted in perturbed IgA plasma cell compartmentalization, characterized by the absence of IgA plasma cells in the bone marrow, their reductions in the spleen, the blood and the lamina propria of the colon and the small intestine, concomitant with their accumulation and retention in mesenteric lymph nodes and Peyer’s patches. Most intriguingly, secretory IgA in the intestinal lumen was almost absent, dimeric serum IgA was drastically reduced and antigen-specific IgA responses to soluble Salmonella flagellin were blunted in KLF2-deficient mice. Perturbance of IgA plasma cell localization was caused by deregulation of CCR9, Integrin chains αM, α4, β7, and sphingosine-1-phosphate receptors. Hence, KLF2 not only orchestrates the localization of IgA plasma cells by fine-tuning chemokine receptors and adhesion molecules but also controls IgA responses to Salmonella flagellin.
CRIS-Team Scopus Importer:2022-04-15

Lung cell entry, cell-cell fusion capacity, and neutralisation sensitivity of omicron sublineage BA.2.75 - Arora, Prerna; Nehlmeier, Inga; Kempf, Amy; Cossmann, Anne; Schulz, Sebastian; Dopfer-Jablonka, Alexandra; Baier, Eva; Tampe, Björn; Moerer, Onnen; Dickel, Steffen; Winkler, Martin S.; Jäck, Hans-Martin; et al. (Lancet Infectious Diseases, 2022)
CRIS-Team Scopus Importer:2022-11-11

miR-148a controls metabolic programming and survival of mature CD19-negative plasma cells in mice - Pracht, Katharina; Meinzinger, Julia; Schulz, Sebastian; Daum, Patrick; Corte-Real, Joana; Hauke, Manuela; Roth, Eduard; Kindermann, Dorothea; Mielenz, Dirk; Schuh, Wolfgang; Wittmann, Jürgen; Jäck, Hans-Martin (European Journal of Immunology, 2021)
Long-lived antibody-secreting plasma cells are essential to establish humoral memory against pathogens. While a regulatory transcription factor network has been established in plasma cell differentiation, the regulatory role of miRNAs remains enigmatic. We have recently identified miR-148a as the most abundant miRNA in primary mouse and human plasma cells. To determine whether this plasma cell signature miRNA controls the in vivo development of B cells into long-lived plasma cells, we established mice with genomic, conditional, and inducible deletions of miR-148a. The analysis of miR-148a-deficient mice revealed reduced serum Ig, decreased numbers of newly formed plasmablasts and reduced CD19-negative, CD93-positive long-lived plasma cells. Transcriptome and metabolic analysis revealed an impaired glucose uptake, a reduced oxidative phosphorylation-based energy metabolism, and an altered abundance of homing receptors CXCR3 (increase) and CXCR4 (reduction) in miR-148a-deficient plasma cells. These findings support the role of miR-148a as a positive regulator of the maintenance of long-lived plasma cells.
CRIS-Team Scopus Importer:2021-02-05
Keywords: CXC receptors; Glut-1; miR-148a; Oxidative phosphorylation; Plasma cells

Mitochondrial respiration in B lymphocytes is essential for humoral immunity by controlling the flux of the TCA cycle - Urbanczyk, Sophia; Baris, Olivier R.; Hofmann, Jörg; Taudte, Verena; Guegen, Naïg; Golombek, Florian; Castiglione, Kathrin; Meng, Xianyi; Bozec, Aline; Thomas, Jana; Weckwerth, Leonie; Mougiakakos, Dimitrios; et al. (Cell Reports, 2022)
To elucidate the function of oxidative phosphorylation (OxPhos) during B cell differentiation, we employ CD23Cre-driven expression of the dominant-negative K320E mutant of the mitochondrial helicase Twinkle (DNT). DNT-expression depletes mitochondrial DNA during B cell maturation, reduces the abundance of respiratory chain protein subunits encoded by mitochondrial DNA, and, consequently, respiratory chain super-complexes in activated B cells. Whereas B cell development in DNT mice is normal, B cell proliferation, germinal centers, class switch to IgG, plasma cell maturation, and T cell-dependent as well as T cell-independent humoral immunity are diminished. DNT expression dampens OxPhos but increases glycolysis in lipopolysaccharide and B cell receptor-activated cells. Lipopolysaccharide-activated DNT-B cells exhibit altered metabolites of glycolysis, the pentose phosphate pathway, and the tricarboxylic acid cycle and a lower amount of phosphatidic acid. Consequently, mTORC1 activity and BLIMP1 induction are curtailed, whereas HIF1α is stabilized. Hence, mitochondrial DNA controls the metabolism of activated B cells via OxPhos to foster humoral immunity.
CRIS-Team Scopus Importer:2022-06-17
Keywords: B lymphocyte; class switch recombination; CP: Immunology; germinal center; HIF1; hypoxia inducible factor 1; mammalian target of Rapamycin; mitochondrial DNA; mitochondrial respiration; mTOR; oxidative phosphorylation; phosphatidic acid; plasma cell; TCA cycle

Neutralisation sensitivity of SARS-CoV-2 lineages EG.5.1 and XBB.2.3 - Zhang, Lu; Kempf, Amy; Nehlmeier, Inga; Cossmann, Anne; Dopfer-Jablonka, Alexandra; Stankov, Metodi V.; Schulz, Sebastian; Jäck, Hans-Martin; Behrens, Georg M.N.; Pöhlmann, Stefan; Hoffmann, Markus (Lancet Infectious Diseases, 2023)
CRIS-Team Scopus Importer:2023-10-13

Neutralisation sensitivity of the SARS-CoV-2 XBB.1 lineage - Arora, Prerna; Cossmann, Anne; Schulz, Sebastian; Ramos, Gema Morillas; Stankov, Metodi V.; Jäck, Hans-Martin; Behrens, Georg M.N.; Pöhlmann, Stefan; Hoffmann, Markus (Lancet Infectious Diseases, 2023)
CRIS-Team Scopus Importer:2023-02-10

No evidence for increased cell entry or antibody evasion by Delta sublineage AY.4.2 - Arora, Prerna; Kempf, Amy; Nehlmeier, Inga; Graichen, Luise; Winkler, Martin S.; Lier, Martin; Schulz, Sebastian; Jäck, Hans-Martin; Poehlmann, Stefan; Hoffmann, Markus (Cellular & Molecular Immunology, 2022)
Since the beginning of the COVID-19 pandemic, multiple SARS-CoV-2 variants have emerged. While some variants spread only locally, others, referred to as variants of concern, disseminated globally and became drivers of the pandemic. All SARS-CoV-2 variants harbor mutations relative to the virus circulating early in the pandemic, and mutations in the viral spike (S) protein are considered of particular relevance since the S protein mediates host cell entry and constitutes the key target of the neutralizing antibody response. As a consequence, mutations in the S protein may increase SARS-CoV-2 infectivity and enable its evasion of neutralizing antibodies. Furthermore, mutations in the S protein can modulate viral transmissibility and pathogenicity.
CRIS-Team Scopus Importer:2022-01-14
Keywords: Antibody evasion; AY.4.2; Delta; Host cell entry; SARS-CoV-2

Omicron sublineage BQ.1.1 resistance to monoclonal antibodies - Arora, Prerna; Kempf, Amy; Nehlmeier, Inga; Schulz, Sebastian; Jäck, Hans-Martin; Pöhlmann, Stefan; Hoffmann, Markus (Lancet Infectious Diseases, 2023)
CRIS-Team Scopus Importer:2023-01-06

PLD3 and PLD4 are single-stranded acid exonucleases that regulate endosomal nucleic-acid sensing - Gavin, Amanda L.; Huang, Deli; Huber, Christoph; Martensson, Annica; Tardif, Virginie; Skog, Patrick D.; Blane, Tanya R.; Thinnes, Therese C.; Osborn, Kent; Chong, Hayley S.; Kargaran, Farnaz; Kimm, Phoebe; et al. (Nature Immunology, 2018)
The sensing of microbial genetic material by leukocytes often elicits beneficial pro-inflammatory cytokines, but dysregulated responses can cause severe pathogenesis. Genome-wide association studies have linked the gene encoding phospholipase D3 (PLD3) to Alzheimer's disease and have linked PLD4 to rheumatoid arthritis and systemic sclerosis. PLD3 and PLD4 are endolysosomal proteins whose functions are obscure. Here, PLD4-deficient mice were found to have an inflammatory disease, marked by elevated levels of interferon-γ (IFN-γ) and splenomegaly. These phenotypes were traced to altered responsiveness of PLD4-deficient dendritic cells to ligands of the single-stranded DNA sensor TLR9. Macrophages from PLD3-deficient mice also had exaggerated TLR9 responses. Although PLD4 and PLD3 were presumed to be phospholipases, we found that they are 5' exonucleases, probably identical to spleen phosphodiesterase, that break down TLR9 ligands. Mice deficient in both PLD3 and PLD4 developed lethal liver inflammation in early life, which indicates that both enzymes are needed to regulate inflammatory cytokine responses via the degradation of nucleic acids.
EVALuna2:214389

Profound neutralization evasion and augmented host cell entry are hallmarks of the fast-spreading SARS-CoV-2 lineage XBB.1.5 - Hoffmann, Markus; Arora, Prerna; Nehlmeier, Inga; Kempf, Amy; Cossmann, Anne; Schulz, Sebastian; Morillas Ramos, Gema; Manthey, Luis A.; Jäck, Hans-Martin; Behrens, Georg M.N.; Pöhlmann, Stefan (Cellular & Molecular Immunology, 2023)
CRIS-Team Scopus Importer:2023-03-17

SARS-CoV-2 BA.2.86 enters lung cells and evades neutralizing antibodies with high efficiency - Zhang, Lu; Kempf, Amy; Nehlmeier, Inga; Cossmann, Anne; Richter, Anja; Bdeir, Najat; Graichen, Luise; Moldenhauer, Anna Sophie; Dopfer-Jablonka, Alexandra; Stankov, Metodi V.; Simon-Loriere, Etienne; Schulz, Sebastian; et al. (Cell, 2024)
BA.2.86, a recently identified descendant of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron BA.2 sublineage, contains ∼35 mutations in the spike (S) protein and spreads in multiple countries. Here, we investigated whether the virus exhibits altered biological traits, focusing on S protein-driven viral entry. Employing pseudotyped particles, we show that BA.2.86, unlike other Omicron sublineages, enters Calu-3 lung cells with high efficiency and in a serine- but not cysteine-protease-dependent manner. Robust lung cell infection was confirmed with authentic BA.2.86, but the virus exhibited low specific infectivity. Further, BA.2.86 was highly resistant against all therapeutic antibodies tested, efficiently evading neutralization by antibodies induced by non-adapted vaccines. In contrast, BA.2.86 and the currently circulating EG.5.1 sublineage were appreciably neutralized by antibodies induced by the XBB.1.5-adapted vaccine. Collectively, BA.2.86 has regained a trait characteristic of early SARS-CoV-2 lineages, robust lung cell entry, and evades neutralizing antibodies. However, BA.2.86 exhibits low specific infectivity, which might limit transmissibility.
CRIS-Team Scopus Importer:2024-02-16
Keywords: antibody evasion; BA.2.86; fusion; infectivity; lung cell entry; mutations; pirola variant; SARS-CoV-2; Spike protein; TMPRSS2

SARS-CoV-2 mutations acquired in mink reduce antibody-mediated neutralization - Hoffmann, Markus; Zhang, Lu; Krüger, Nadine; Graichen, Luise; Kleine-Weber, Hannah; Hofmann-Winkler, Heike; Kempf, Amy; Nessler, Stefan; Riggert, Joachim; Winkler, Martin Sebastian; Schulz, Sebastian; Jäck, Hans-Martin; et al. (Cell Reports, 2021)
Transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from humans to farmed mink has been observed in Europe and the US. In the infected animals, viral variants arose that harbored mutations in the spike (S) protein, the target of neutralizing antibodies, and these variants were transmitted back to humans. This raised concerns that mink might become a constant source of human infection with SARS-CoV-2 variants associated with an increased threat to human health and resulted in mass culling of mink. Here, we report that mutations frequently found in the S proteins of SARS-CoV-2 from mink are mostly compatible with efficient entry into human cells and its inhibition by soluble angiotensin-converting enzyme 2 (ACE2). In contrast, mutation Y453F reduces neutralization by an antibody with emergency use authorization for coronavirus disease 2019 (COVID-19) therapy and sera/plasma from COVID-19 patients. These results suggest that antibody responses induced upon infection or certain antibodies used for treatment might offer insufficient protection against SARS-CoV-2 variants from mink.
CRIS-Team Scopus Importer:2021-04-23
Keywords: antibodies; evasion; mink; mutation; neutralization; SARS-CoV-2; spike protein; variant; Y453F

SARS-CoV-2 Omicron sublineages show comparable cell entry but differential neutralization by therapeutic antibodies - Arora, Prerna; Zhang, Lu; Krüger, Nadine; Rocha, Cheila; Sidarovich, Anzhalika; Schulz, Sebastian; Kempf, Amy; Graichen, Luise; Moldenhauer, Anna Sophie; Cossmann, Anne; Dopfer-Jablonka, Alexandra; Behrens, Georg M.N.; et al. (Cell Host & Microbe, 2022)
The Omicron variant of SARS-CoV-2 evades antibody-mediated neutralization with unprecedented efficiency. At least three Omicron sublineages have been identified—BA.1, BA.2, and BA.3—and BA.2 exhibits increased transmissibility. However, it is currently unknown whether BA.2 differs from the other sublineages regarding cell entry and antibody-mediated inhibition. Here, we show that BA.1, BA.2, and BA.3 enter and fuse target cells with similar efficiency and in an ACE2-dependent manner. However, BA.2 was not efficiently neutralized by seven of eight antibodies used for COVID-19 therapy, including Sotrovimab, which robustly neutralized BA.1. In contrast, BA.2 and BA.3 (but not BA.1) were appreciably neutralized by Cilgavimab, which could constitute a treatment option. Finally, all sublineages were comparably and efficiently neutralized by antibodies induced by BNT162b2 booster vaccination after previous two-dose homologous or heterologous vaccination. Collectively, the Omicron sublineages show comparable cell entry and neutralization by vaccine-induced antibodies but differ in susceptibility to therapeutic antibodies.
CRIS-Team Scopus Importer:2022-08-19
Keywords: ACE2; antibody; neutralization; Omicron; SARS-CoV-2; sotrovimab; spike; vaccine

SARS-CoV-2 variant B.1.617 is resistant to bamlanivimab and evades antibodies induced by infection and vaccination - Hoffmann, Markus; Hofmann-Winkler, Heike; Krüger, Nadine; Kempf, Amy; Nehlmeier, Inga; Graichen, Luise; Arora, Prerna; Sidarovich, Anzhalika; Moldenhauer, Anna Sophie; Winkler, Martin S.; Schulz, Sebastian; Jäck, Hans-Martin; et al. (Cell Reports, 2021)
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants threatens efforts to contain the coronavirus disease 2019 (COVID-19) pandemic. The number of COVID-19 cases and deaths in India has risen steeply, and a SARS-CoV-2 variant, B.1.617, is believed to be responsible for many of these cases. The spike protein of B.1.617 harbors two mutations in the receptor binding domain, which interacts with the angiotensin converting enzyme 2 (ACE2) receptor and constitutes the main target of neutralizing antibodies. Therefore, we analyze whether B.1.617 is more adept in entering cells and/or evades antibody responses. B.1.617 enters two of eight cell lines tested with roughly 50% increased efficiency and is equally inhibited by two entry inhibitors. In contrast, B.1.617 is resistant against bamlanivimab, an antibody used for COVID-19 treatment. B.1.617 evades antibodies induced by infection or vaccination, although less so than the B.1.351 variant. Collectively, our study reveals that antibody evasion of B.1.617 may contribute to the rapid spread of this variant.
CRIS-Team Scopus Importer:2021-07-30
Keywords: antibodies; B.1.617; cell entry; convalescence; immune evasion; mutations; SARS-CoV-2; spike protein; vaccination

SARS-CoV-2 variants B.1.351 and P.1 escape from neutralizing antibodies - Hoffmann, Markus; Arora, Prerna; Groß, Rüdiger; Seidel, Alina; Hörnich, Bojan F.; Hahn, Alexander S.; Krüger, Nadine; Graichen, Luise; Hofmann-Winkler, Heike; Kempf, Amy; Winkler, Martin S.; Schulz, Sebastian; et al. (Cell, 2021)
The global spread of SARS-CoV-2/COVID-19 is devastating health systems and economies worldwide. Recombinant or vaccine-induced neutralizing antibodies are used to combat the COVID-19 pandemic. However, the recently emerged SARS-CoV-2 variants B.1.1.7 (UK), B.1.351 (South Africa), and P.1 (Brazil) harbor mutations in the viral spike (S) protein that may alter virus-host cell interactions and confer resistance to inhibitors and antibodies. Here, using pseudoparticles, we show that entry of all variants into human cells is susceptible to blockade by the entry inhibitors soluble ACE2, Camostat, EK-1, and EK-1-C4. In contrast, entry of the B.1.351 and P.1 variant was partially (Casirivimab) or fully (Bamlanivimab) resistant to antibodies used for COVID-19 treatment. Moreover, entry of these variants was less efficiently inhibited by plasma from convalescent COVID-19 patients and sera from BNT162b2-vaccinated individuals. These results suggest that SARS-CoV-2 may escape neutralizing antibody responses, which has important implications for efforts to contain the pandemic.
CRIS-Team Scopus Importer:2021-04-23
Keywords: antibodies; B.1.1.7; B.1.351; COVID-19; escape; host cell entry; neutralization; P.1; SARS-CoV-2; spike protein; variants; variants of concern; VOC

SARS-CoV-2 variants C.1.2 and B.1.621 (Mu) partially evade neutralization by antibodies elicited upon infection or vaccination - Arora, Prerna; Kempf, Amy; Nehlmeier, Inga; Graichen, Luise; Winkler, Martin S.; Lier, Martin; Schulz, Sebastian; Jäck, Hans-Martin; Cossmann, Anne; Stankov, Metodi V.; Behrens, Georg M.N.; Pöhlmann, Stefan; et al. (Cell Reports, 2022)
Rapid spread of SARS-CoV-2 variants C.1.2 and B.1.621 (Mu variant) in Africa and the Americas, respectively, as well as a high number of mutations in the viral spike proteins raised concerns that these variants might pose an elevated threat to human health. Here, we show that C.1.2 and B.1.621 spike proteins mediate increased entry into certain cell lines but do not exhibit increased ACE2 binding. Further, we demonstrate that C.1.2 and B.1.621 are resistant to neutralization by bamlanivimab but remain sensitive to inhibition by antibody cocktails used for COVID-19 therapy. Finally, we show that C.1.2 and B.1.621 partially escape neutralization by antibodies induced upon infection and vaccination, with escape of vaccine-induced antibodies being as potent as that measured for B.1.351 (Beta variant), which is known to be highly neutralization resistant. Collectively, C.1.2 and B.1.621 partially evade control by vaccine-induced antibodies, suggesting that close monitoring of these variants is warranted.
CRIS-Team Scopus Importer:2022-05-27
Keywords: antibody; B.1.621; C.1.2; COVID-19; CP: Immunology; CP: Microbiology; Mu; neutralization; SARS-CoV-2; spike; variants

TFG is required for autophagy flux and to prevent endoplasmic reticulum stress in CH12 B lymphoma cells - Steinmetz, Tobit; Schlötzer-Schrehardt, Ursula; Hearne, Abigail; Schuh, Wolfgang; Wittner, Jens; Schulz, Sebastian; Winkler, Thomas; Jäck, Hans-Martin; Mielenz, Dirk (Autophagy, 2020)
Plasma cells depend on quality control of newly synthesized antibodies in the endoplasmic reticulum (ER) via macroautophagy/autophagy and proteasomal degradation. The cytosolic adaptor protein TFG (Trk-fused gene) regulates ER-Golgi transport, the secretory pathway and proteasome activity in non-immune cells. We show here that TFG is upregulated during lipopolysaccharide- and CpG-induced differentiation of B1 and B2 B cells into plasmablasts, with the highest expression of TFG in mature plasma cells. CRISPR-CAS9-mediated gene disruption of tfg in the B lymphoma cell line CH12 revealed increased apoptosis, which was reverted by BCL2 but even more by ectopic TFG expression. Loss of TFG disrupted ER structure, leading to an expanded ER and increased expression of ER stress genes. When compared to wild-type CH12 cells, tfg KO CH12 cells were more sensitive toward ER stress induced by tunicamycin, monensin and proteasome inhibition or by expression of an ER-bound immunoglobulin (Ig) μ heavy (µH) chain. CH12 tfg KO B cells displayed more total LC3, lower LC3-II turnover and increased numbers and size of autophagosomes. Tandem-fluorescent-LC3 revealed less accumulation of GFP-LC3 in starved and chloroquine-treated CH12 tfg KO B cells. The GFP:RFP ratio of tandem-fluorescent-LC3 was higher in tunicamycin-treated CH12 tfg KO B cells, suggesting less autophagy flux during induced ER stress. Based on these data, we suggest that TFG controls autophagy flux in CH12 B cells and propose that TFG is a survival factor that alleviates ER stress through the support of autophagy flux in activated B cells and mature plasma cells.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Antibody; apoptosis; autophagy; autophagy flux; B cell; B1 B cell; endoplasmic reticulum stress; immunoglobulin; plasma cell; Trk-fused gene

The BCMA:Tomato Mouse - a new reporter to characterize long-lived plasma cells - Schulz, Sebastian; Wittner, Jens; Kueh, Andrew J.; Pal, Martin; Herold, Marko J.; Schuh, Wolfgang; Jäck, Hans-Martin (JOURNAL OF IMMUNOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-08

The microprocessor component, DGCR8, is essential for early B-cell development in mice - Brandl, Andreas; Daum, Patrick; Brenner, Sven; Schulz, Sebastian; Yap, Desmond Yat Hin; Boesl, Michael R.; Wittmann, Jürgen; Schuh, Wolfgang; Jäck, Hans-Martin (European Journal of Immunology, 2016)
microRNAs (miRNAs) are important posttranscriptional regulators during hematopoietic lineage commitment and lymphocyte development. Mature miRNAs are processed from primary miRNA transcripts in two steps by the microprocessor complex, consisting of Drosha and its partner DiGeorge Critical Region 8 (DGCR8), and the RNAse III enzyme, Dicer. Conditional ablations of Drosha and Dicer have established the importance of both RNAses in B- and T-cell development. Here, we show that a cre-mediated B-cell specific deletion of DGCR8 in mice results in a nearly complete maturation block at the transition from the pro-B to the pre-B cell stage, and a failure to upregulate Ig ? heavy chain expression in pro-B cells. Furthermore, we found that the death of freshly isolated DGCR8-deficient pro-B cells could be partially prevented by enforced Bcl2 expression. We conclude from these findings that the microprocessor component DGCR8 is essential for survival and differentiation of early B-cell progenitors.
EVALuna2:13647

The microRNA processing subunit DGCR8 is required for a T cell-dependent germinal center response - Daum, Patrick; Ottmann, Shannon; Meinzinger, Julia; Schulz, Sebastian; Corte-Real, Joana; Hauke, Manuela; Roth, Edith; Schuh, Wolfgang; Mielenz, Dirk; Jäck, Hans-Martin; Pracht, Katharina (Frontiers in Immunology, 2022)
We have previously shown that the microRNA (miRNA) processor complex consisting of the RNAse Drosha and the DiGeorge Critical Region (DGCR) 8 protein is essential for B cell maturation. To determine whether miRNA processing is required to initiate T cell-mediated antibody responses, we deleted DGCR8 in maturing B2 cells by crossing a mouse with loxP-flanked DGCR8 alleles with a CD23-Cre mouse. As expected, non-immunized mice showed reduced numbers of mature B2 cells and IgG-secreting cells and diminished serum IgG titers. In accordance, germinal centers and antigen-specific IgG-secreting cells were absent in mice immunized with T-dependent antigens. Therefore, DGCR8 is required to mount an efficient T-dependent antibody response. However, DGCR8 deletion in B1 cells was incomplete, resulting in unaltered B1 cell numbers and normal IgM and IgA titers in DGCR8-knock-out mice. Therefore, this mouse model could be used to analyze B1 responses in the absence of functional B2 cells.
CRIS-Team WoS Importer:2023-01-27

The Omicron variant is highly resistant against antibody-mediated neutralization: Implications for control of the COVID-19 pandemic - Hoffmann, Markus; Krüger, Nadine; Schulz, Sebastian; Cossmann, Anne; Rocha, Cheila; Kempf, Amy; Nehlmeier, Inga; Graichen, Luise; Moldenhauer, Anna Sophie; Winkler, Martin S.; Lier, Martin; Dopfer-Jablonka, Alexandra; et al. (Cell, 2022)
The rapid spread of the SARS-CoV-2 Omicron variant suggests that the virus might become globally dominant. Further, the high number of mutations in the viral spike protein raised concerns that the virus might evade antibodies induced by infection or vaccination. Here, we report that the Omicron spike was resistant against most therapeutic antibodies but remained susceptible to inhibition by sotrovimab. Similarly, the Omicron spike evaded neutralization by antibodies from convalescent patients or individuals vaccinated with the BioNTech-Pfizer vaccine (BNT162b2) with 12- to 44-fold higher efficiency than the spike of the Delta variant. Neutralization of the Omicron spike by antibodies induced upon heterologous ChAdOx1 (Astra Zeneca-Oxford)/BNT162b2 vaccination or vaccination with three doses of BNT162b2 was more efficient, but the Omicron spike still evaded neutralization more efficiently than the Delta spike. These findings indicate that most therapeutic antibodies will be ineffective against the Omicron variant and that double immunization with BNT162b2 might not adequately protect against severe disease induced by this variant.
CRIS-Team Scopus Importer:2022-01-28
Keywords: antibody; immune evasion; neutralization; Omicron; SARS-CoV-2; spike; vaccine

The role of Kruppel-Like-Factor 2 (KLF2) in plasma cell homeostasis - Wittner, Jens; Schulz, Sebastian; Jäck, Hans-Martin; Schuh, Wolfgang (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

The spike protein of SARS-CoV-2 variant A.30 is heavily mutated and evades vaccine-induced antibodies with high efficiency - Arora, Prerna; Rocha, Cheila; Kempf, Amy; Nehlmeier, Inga; Graichen, Luise; Winkler, Martin S.; Lier, Martin; Schulz, Sebastian; Jäck, Hans-Martin; Cossmann, Anne; Stankov, Metodi V.; Behrens, Georg M. N.; et al. (Cellular & Molecular Immunology, 2021)
CRIS-Team Scopus Importer:2021-11-05

Virological Traits of the SARS-CoV-2 BA.2.87.1 Lineage - Zhang, Lu; Dopfer-Jablonka, Alexandra; Nehlmeier, Inga; Kempf, Amy; Graichen, Luise; Calderón Hampel, Noemí; Cossmann, Anne; Stankov, Metodi V.; Morillas Ramos, Gema; Schulz, Sebastian; Jäck, Hans-Martin; Behrens, Georg M.N.; et al. (Vaccines, 2024)
Transmissibility and immune evasion of the recently emerged, highly mutated SARS-CoV-2 BA.2.87.1 are unknown. Here, we report that BA.2.87.1 efficiently enters human cells but is more sensitive to antibody-mediated neutralization than the currently dominating JN.1 variant. Acquisition of adaptive mutations might thus be needed for efficient spread in the population.
CRIS-Team Scopus Importer:2024-05-31
Keywords: ACE2 binding; antibody evasion; BA.2.87.1; host cell entry; SARS-CoV-2; spike protein